Representación Artística de los Paisajes Amazónicos de la reserva de producción Faunística Cuyabeno, utilizando la técnica de la pintura en acuarela - Cadena Cabrera, Verónica Liliana (2019)
The research work had the fundamental purpose of performing the ARTISTIC REPRESENTATION OF THE AMAZON LANDSCAPES OF THE CUYABENO FAUNISTIC PRODUCTION RESERVE, USING THE PAINTING TECHNIQUE IN AQUARELA, making an in-depth analysis of the experience, customs and traditions of the five indigenous nationalities located in the Cuyabeno Fauna Production Reserve, such as Sionas, Cofanes, Qhichwas, SecoyasShuar. To carry out the research, several visits were made to the indigenous communities of the Cuyabeno Faunistic Reserve. The type of research to be carried out was determined by: the level (bibliographic field and argumentative) because the characteristics of the subject require it, the method I used was bibliographic, analytical, historical, to collect the information in the exact place of the facts, using the survey technique with a questionnaire addressed to 5 people of the five Indigenous nationalities. Through field research, results were obtained that proved the hypothesis and justified the need to look for alternatives to encourage the population of flora and fauna in the Cuyabeno Fauna Reserve, since it is a beautiful tourist attraction.